2015
DOI: 10.1159/000439536
|View full text |Cite
|
Sign up to set email alerts
|

FGFR4 Is a Potential Predictive Biomarker in Oral and Oropharyngeal Squamous Cell Carcinoma

Abstract: Objective: The aim of this study was to investigate whether fibroblast growth factor receptor 4 (FGFR4) could serve as a potential therapeutic target, prognostic biomarker or biomarker predicting radiotherapy sensitivity in oral squamous cell carcinoma (OSCC) and oropharyngeal squamous cell carcinoma (OPSCC). Methods: FGFR4 immunohistochemistry and FGFR4/CEN5q FISH were performed on tissue microarrays from 212 OSCC and 238 OPSCC patients. FGFR4 genotypes were determined by PCR and DNA sequencing in 76 random O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…FGFR4, the direct receptor of FGF19 and predominately expressed in liver tissues, was reported to be highly expressed in oral and oropharyngeal squamous cell carcinoma with a frequent Gly388Arg SNP [19]. Similar findings were reported in intrahepatic cholangiocarcinoma [20], colorectal cancer [21], and hepatocellular carcinoma [22].…”
Section: Introductionsupporting
confidence: 67%
“…FGFR4, the direct receptor of FGF19 and predominately expressed in liver tissues, was reported to be highly expressed in oral and oropharyngeal squamous cell carcinoma with a frequent Gly388Arg SNP [19]. Similar findings were reported in intrahepatic cholangiocarcinoma [20], colorectal cancer [21], and hepatocellular carcinoma [22].…”
Section: Introductionsupporting
confidence: 67%
“…Recently, FGF19‐FGFR4 has drawn increasing attention in carcinogenesis. Previous research has found that FGFR4 is overexpressed in multiple tumors, such as breast cancer, pancreatic carcinomas, and oral squamous cell carcinoma . The high levels of FGFR4 in nasopharyngeal carcinoma and CRC contributed to tumor cell proliferation and metastasis .…”
Section: Discussionmentioning
confidence: 96%
“…Particularly, FGFR4 expression was significantly upregulated in most liver cancer cases, and enhanced FGF19-FGFR4 signaling is linked to HCC progression, metastasis, and poor survival (Sawey et al, 2011). Although high expression of FGFR4 was observed in OPSCC and pancreatic cancer, FGFR4 does not show prognostic significance in these cancers (Motoda et al, 2011;Koole et al, 2015).…”
Section: Molecular Characteristics Of Fgfr4mentioning
confidence: 99%
“…FGF19 binds to FGFR4 and activates GSK3β-Nrf2 signaling cascade to exert cytoprotective role against ER stress in HCC . It has been reported that both rearranged distal enhancement regions and point mutations in the proximal promoter region might cause FGFR4 overexpression (Koole et al, 2015). Moreover, inhibition of miRNAs targeting FGFR4 or aberrant long noncoding RNA (lncRNA) expression leads to FGFR4 overexpression (Masaru, 2016).…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%